2010
DOI: 10.1371/journal.pone.0009025
|View full text |Cite
|
Sign up to set email alerts
|

Complete-Proteome Mapping of Human Influenza A Adaptive Mutations: Implications for Human Transmissibility of Zoonotic Strains

Abstract: BackgroundThere is widespread concern that H5N1 avian influenza A viruses will emerge as a pandemic threat, if they become capable of human-to-human (H2H) transmission. Avian strains lack this capability, which suggests that it requires important adaptive mutations. We performed a large-scale comparative analysis of proteins from avian and human strains, to produce a catalogue of mutations associated with H2H transmissibility, and to detect their presence in avian isolates.Methodology/Principal FindingsWe cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(113 citation statements)
references
References 69 publications
(63 reference statements)
4
108
1
Order By: Relevance
“…A number of viral determinants have been identified that contribute to the adaptation of avian influenza viruses to mammalian hosts , and several large-scale comparative analyses of proteins from avian and human viruses have been performed to cat-alog the amino acids that are conserved in each host species (29)(30)(31). The PB2, PB1, and PA subunits of the polymerase complex play a major role in virus pathogenicity and efficient viral growth in mammals.…”
mentioning
confidence: 99%
“…A number of viral determinants have been identified that contribute to the adaptation of avian influenza viruses to mammalian hosts , and several large-scale comparative analyses of proteins from avian and human viruses have been performed to cat-alog the amino acids that are conserved in each host species (29)(30)(31). The PB2, PB1, and PA subunits of the polymerase complex play a major role in virus pathogenicity and efficient viral growth in mammals.…”
mentioning
confidence: 99%
“…Th is complex, unlike the surface antigens HA and NA, is highly conserved among all IAVs. However, the hostadaptation mutations were found in all subunits of viral RNA polymerase (Miotto et al, 2010). In general, they correlate with enhanced replication ability of avian viruses in mammals.…”
Section: Other Iav Proteins Infl Uencing the Virulencementioning
confidence: 98%
“…Similarly, Figure 5 showed that the correlation of nuclear localization signals (NLS) of PB2 was the strongest in avian, human, and pandemic 2009 H1N1, and the correlation of the RNA cap binding domain of PB2 was the strongest in swine. To further quantify the correlation of these four proteins, the averaged counts of positions in the functional domains of the four proteins that had a positive MI value with other positions were calculated, based on the domain boundary information given in [21] (Figure 5). Comprehensive phylogenetic analysis suggested that the genes of 2009 pandemic H1N1 were derived from avian (PB2 and PA), human H3N2 (PB1), classical swine (HA, NP and NS), and …”
Section: Correlation Within Each Individual Protein and Between Proteinsmentioning
confidence: 99%
“…In a sense, the correlation information obtained from task two was pair dependent, i.e., it was about pairs. The third task was to mine the association of these four proteins with a pair independent approach, where the locations of pairs with positive MI values were counted according to each protein or to each functional domain in a protein as described in [21]. The strength of association was measured by the averaged counts of correlated pairs located within each protein or between proteins.…”
Section: Introductionmentioning
confidence: 99%